2019
DOI: 10.1038/s41598-019-44672-8
|View full text |Cite
|
Sign up to set email alerts
|

Transferability of PCR-based diagnostic protocols: An international collaborative case study assessing protocols targeting the quarantine pine pathogen Fusarium circinatum

Abstract: Fusarium circinatum is a harmful pathogenic fungus mostly attacking Pinus species and also Pseudotsuga menziesii , causing cankers in trees of all ages, damping-off in seedlings, and mortality in cuttings and mother plants for clonal production. This fungus is listed as a quarantine pest in several parts of the world and the trade of potentially contaminated pine material such as cuttings, seedlings or seeds is restricted in order to prevent its spread t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 46 publications
2
25
0
1
Order By: Relevance
“…Although a test is sometimes very efficient in the initial conditions of development, it is conceivable to imagine that the performance of a qPCR or PCR detection protocol may vary if the conditions of use differ from those of the development team (Grosdidier et al 2017). In a study focused on the transferability of molecular test detection, in the pine pathogen Fusarium circinatum, Ioos et al (2019a) showed that changes in reagents, equipment, and qPCR fluorescence data processing software could have major effects on the reliability of the results (false positives and false negatives). Much of the variance produced in qPCR results (expressed as Ct values) is not simply due to reagent changes.…”
Section: Development and Validation Of Molecular Diagnostic Methodsmentioning
confidence: 99%
“…Although a test is sometimes very efficient in the initial conditions of development, it is conceivable to imagine that the performance of a qPCR or PCR detection protocol may vary if the conditions of use differ from those of the development team (Grosdidier et al 2017). In a study focused on the transferability of molecular test detection, in the pine pathogen Fusarium circinatum, Ioos et al (2019a) showed that changes in reagents, equipment, and qPCR fluorescence data processing software could have major effects on the reliability of the results (false positives and false negatives). Much of the variance produced in qPCR results (expressed as Ct values) is not simply due to reagent changes.…”
Section: Development and Validation Of Molecular Diagnostic Methodsmentioning
confidence: 99%
“…A recent collaborative study joined 23 partners to assess the transferability and performance of nine different protocols (conventional PCR and real-time PCR) using a wide panel of F. circinatum and other Fusarium spp. DNA [89].…”
Section: Molecular Methods For Pathogen Detectionmentioning
confidence: 99%
“…Since the test requires the simultaneous amplification of two unrelated but specific regions of the F. circinatum genome, it has been suggested that it brings additional reliability. The conventional PCR tests described above are easy to set up and need less expensive equipment than qPCR methods, but require an additional electrophoresis step, and thus, more time to obtain a result [89].…”
Section: Diagnosis Using Conventional Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Roman times the history of Europe has been characterised by an intense trade across continents that has resulted in the introduction of many non-native tree species, such as Sweet chestnut from western Asia (Adua 1999), and also of pests of woody plants (Santini et al 2018). PRA and PEQ are worth to be applied, even where are not compulsory, to strengthen a prevention to pest introduction based only on diagnostic procedures (Ioos et al 2019). PEQ can be implemented in a variety of ways, ranging from secure quarantine greenhouses to surveyed open-field plantations, depending on country and perceived risk.…”
Section: Importmentioning
confidence: 99%